Geographical distribution of Tabanomorpha (Diptera, Brachycera): Athericidae, Rhagionidae, Vermileonidae, and small families - Santos, Charles Morphy Dias (EntomoBrasilis, 2008)
The infraorder Tabanomorpha traditionally includes the families Tabanidae, Athericidae, Rhagionidae, and Vermileonidae. The new family Oreoleptidae was placed among the tabanomorphan,as well as some controversial groups as Austroleptidae and Spaniidae, but thereis no agreement on the phylogenetic relationships of the groups considered asbelonging to the infraorder. Here is presented the geographical distribution ofthe following tabanomorphan families: Rhagionidae, Vermileonidae, Athericidae,Austroleptidae and Oreoleptidae. Every historical biogeographical analysisdepends on up-to-dated distributional information, and, hence, reliable listsof distribution are a starting point to a broad comprehension of the evolutionin space.